Adherence to Sars-CoV2 vaccination in hematological patients - Narinx, Justine; Houbiers, Margaux; Seidel, Laurence; Beguin, Yves (Frontiers in Immunology, 2022)
SARS-CoV2 vaccination efficiently prevents severe COVID-19, although hematological patients, particularly under therapy, respond less well. Besides vaccine efficacy, adherence to vaccination is essential for ensuring adequate protection of this vulnerable population. We evaluated the impact of a program aimed at maximizing patient adherence by comparing the rate of SARS-CoV2 vaccination of our hematological patients and a matched sample of the general population. Vaccination rates were 88.9% among 2,156 patients, aged 65.2±15.8 years (M±SD, range 19-86 years). Rates differed considerably with age, i.e. 84.2% between 18-64 years and 92.4% above 65 years (p<0.0001), but not with sex. In the general population, rates were 76.3% overall, 73.0% between 18-64 and 86.7% above 65 years, all significantly lower than among patients, overall (Standardized Incidence ratio (SIR) 1.17; 95%CI 1.12-1.22, p<0.0001) as well as among younger (SIR 1.15; 1.07-1.24, p<0.0001) or older (SIR 1.06; 1.00-1.13, p=0.046) people. Vaccination rates increased to 92.2% overall (SIR 1.21; 1.16-1.27, p<0.0001), 88.5% in younger (SIR 1.21; 1.13-1.30, p<0.0001) and 94.8% in older (SIR 1.09; 1.03-1.12, p=0.0043) patients, after excluding those with medical contraindications, and further to 95.6% overall (SIR 1.26; 1.20-1.32, p<0.0001), 93.8% in younger (SIR 1.29; 1.20-1.38, p<0.0001) and 96.9% in older (SIR 1.11; 1.05-1.18, p=0.0004) patients, after excluding those not seen in hematology in 2021. Vaccination rates were significantly higher in hematological patients compared to the general population regardless of age, sex and municipality. Acceptance of Covid vaccines by hematological patients may be improved by targeted information campaigns carried out by trusted health care professionals.